Identitas Etnik dan Asertivitas Mahasiswa Suku Sunda - Muhammad Zaki Perceka; Irfan Fahmi; Elisa Kurniadewi (Jurnal Psikologi Islam dan Budaya, 2019)
The study was conducted to determine effect of ethnic identity on assertiveness of Sundanese students. The role of students who should be critical and responsive to various things, but less prominent in Sundanese students in consequence of existence of cultural rules require maintaining communication prefer to harbor personal opinions and feelings. The demands of role and acculturation occur on campus lead to high quality of ethnic identity negatively affecting assertive communication skills. The research uses correlational quantitative methods. The results showed the number of Sundanese students with a high level of ethnic identity tended to be more than the low level of ethnic identity. While the quality of assertive communication is high or low is not much different. Using the simple regression calculation method shows that ethnic identity has a positive effect on the assertiveness of Sundanese students.